2014
DOI: 10.1021/bi401644s
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Biophysical Characterization of the CapA Membrane Protein FTT0807 from Francisella tularensis

Abstract: The capA gene (FTT0807) from Francisella tularensis subsp. tularensis SCHU S4 encodes a 44.4 kDa integral membrane protein composed of 403 amino acid residues that is part of an apparent operon that encodes at least two other membrane proteins, CapB, and CapC, which together play a critical role in the virulence and pathogenesis of this bacterium. The capA gene was overexpressed in Escherichia coli as a C-terminal His6-tagged fusion with a folding reporter green fluorescent protein (frGFP). Purification proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 86 publications
0
13
0
Order By: Relevance
“…Many proteins show that the disordered region can be converted into ordered conformation on the addition of neutral salts [35]. On the contrary, it is seen in Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Many proteins show that the disordered region can be converted into ordered conformation on the addition of neutral salts [35]. On the contrary, it is seen in Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, as noted earlier, Apicella et al, found that capB and capC were not involved in LVS capsule production, suggesting that the cap genes perform another function. A more recent study suggested that capA may encode an integral inner membrane protein that interacts with CapB and CapC to export carbohydrates extracellularly (Martin-Garcia et al, 2014 ). Given the large number of genes and operons that have been reported to play roles in F. tularensis capsule production, more studies are clearly needed.…”
Section: Capsulementioning
confidence: 99%
“…Flpp3 has been identified as a virulence determinant (Su et al, 2007), and its atomic resolution structure has recently been determined by NMR (Zook et al, 2015); however, a crystallographic structure has not yet been reported. Proteinase K is a commercially available enzyme belonging to the family of serine proteases, which has been used in numerous studies to identify disordered regions in intrinsically disordered proteins (IDPs;Csizmó k et al, 2005;Denning et al, 2003;Marín et al, 2012;Martin-Garcia et al, 2014;Nyarko et al, 2004). Thaumatin and lysozyme were also included as they crystallize rapidly and easily, and are therefore frequently used as model systems in protein crystallization studies and many proof-of-principle studies.…”
Section: Introductionmentioning
confidence: 99%